Analysis of Musyarakah Contract Practices in Property Financing at BPRS HIK Parahyangan Indramayu - Didik Himmawan; Nurcahyani (Aimmah: Social Sciences Journal, 2025)
This study aims to analyze the practice of musyarakah contracts in property financing implemented by the Sharia People's Financing Bank (BPRS) HIK Parahyangan Indramayu. The main focus of this study is on the profit sharing pattern applied and the standardization of musyarakah contracts used in the financing. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and analysis of related documents. The results of the study indicate that the profit sharing pattern in the musyarakah contract at BPRS HIK Parahyangan Indramayu has been adjusted to sharia principles, by considering fairness and transparency between the bank and the customer. The standardization of musyarakah contracts at this bank includes clear procedures, detailed requirements, and implementation guidelines that refer to the fatwa of the National Sharia Council (DSN-MUI). This study contributes to the development of sharia financing practices in Indonesia, especially in the application of musyarakah contracts in the property sector.